Genome-Wide Association Studies Identifying Multiple Loci Associated With Alfalfa Forage Quality - Lin, Sen; Medina, Cesar Augusto; Norberg, O. Steven; Combs, David; Wang, Guojie; Shewmaker, Glenn; Fransen, Steve; Llewellyn, Don; Yu, Long-Xi (Frontiers in Plant Science, 2021)
Autotetraploid alfalfa is a major hay crop planted all over the world due to its adaptation in different environments and high quality for animal feed. However, the genetic basis of alfalfa quality is not fully understood. In this study, a diverse panel of 200 alfalfa accessions were planted in field trials using augmented experimental design at 3 locations in 2018 and 2019. Thirty-four quality traits were evaluated by Near Infrared Reflectance Spectroscopy (NIRS). The plants were genotyped using genotyping by sequencing (GBS) approach and over 46,000 single nucleotide polymorphisms (SNPs) were obtained after variant calling and filtering. Genome-wide association studies (GWAS) identified twenty-eight SNP markers associated with 16 quality traits. Among them, most of the markers were associated with fiber digestibility and protein content. Phenotypic variations were analyzed from three locations and different sets of markers were identified by GWAS when using phenotypic data from different locations, indicating alfalfa quality traits were also affected by environmental factors. Among different sets of markers identified by location, two markers were associated with 9 traits of fiber digestibility. One marker associated with lignin content was identified consistently in multiple environments. Putative candidate genes underlying fiber-related loci were identified and they are involved in the lignin and cell wall biosynthesis. The DNA markers and associated genes identified in this study will be useful for the genetic improvement of forage quality in alfalfa after validation of the markers.